Bibliometric analysis of high-fidelity simulation training in nursing - Oliveira, Glauber Cavalcante; de Araújo, Aélya Drisana Dias Gomes; da Silva Júnior, Francisco Reginaldo; Barros, Layara Fernandes; dos Santos Sousa, Francisco Wagner; de Galiza, Francisca Tereza (Nurse education today, 2025)
While advances have been made in the field of high-fidelity realistic simulation in nursing, bibliometric studies in this field are limited. The objectives were: (1) to examine the number of articles published in the field of nursing on high-fidelity realistic simulation with a time frame from 2009 to 2023; (2) to identify the scientific journals that publish the most on high-fidelity simulation in nursing; (3) to analyze the authorship of scientific publications on high-fidelity simulation in nursing. This is a bibliometric study of high-fidelity simulation in nursing. The search was carried out in the Web of Science database, using the controlled vocabulary available in the MESH Terms, “High-Fidelity Simulation Training”. To compose the final sample, the following inclusion criteria were taken into account: original article, available in its entirety, involving the training of nursing professionals. Exclusion criteria applied were: review studies, not focusing solely on the training of nursing professionals. A total of 191 manuscripts were obtained. For the selection stage, the EndNote software was used to exclude duplicate studies; sequentially, the studies were exported to the Rayyan software for selection by reading the title and abstract, for subsequent analysis of the studies by the inclusion and exclusion criteria, a total of 72 studies were obtained for analysis. The number of studies on training nursing staff has shown an upward curve over the years. The journals that published the most on the subject over the years were Nurse Education Today (n = 10), Clinical Simulation in Nursing (n = 7) and Healthcare (n = 5). The authors who published the most on the subject were: Arrogante, O (n = 11), Jimenez-Rodriguez, D (n = 6), Carrion-Garcia, L. (n = 3). The concentration of scientific productions on high-fidelity realistic simulation, by author affiliation, has been in Europe and the United States of America, with an increase in publications over the last decade. •Growth in research on simulation in nursing, with emphasis on 2021•Applications of simulation in the teaching and continuous training of nurses•Simulation develops critical thinking by uniting theory and practice in nursing.